The world faces a water crisis — 4 powerful charts show how - Naddaf, Miryam (Nature (London), 2023)
Hundreds of millions of people lack access to safe water and sanitation. Will the first UN conference on water in nearly 50 years make a difference? Hundreds of millions of people lack access to safe water and sanitation. Will the first UN conference on water in nearly 50 years make a difference? Birds-eye view of a group of people walking along desert land in Somalia